Business development of car-restaurant in Malang case study of warung mobil onosogrem - Maharani, Intan Surya; Aliludin, Arson (Journal of Business and Management, 2020)
Abstract. Warung Mobil Onosogrem is one of car-restaurants in Malang. They produce Java traditional dishes and sell them by opening a restaurant in their car. The problem however is that they have not made any big development in sales despite they have run the business for 9 years. Their car which plays a big role in the business is also getting old, causing a hamper to the business. This brings forth the question of if it is economically possible for Warung Mobil Onosogrem to buy a new car and develop the business all at one time. To collect the information needed, a direct interview with the owner of Warung Mobil Onosogrem is used. Data is then used to analyze the marketing and production capacity of the business. From the analysis, alternatives are developed and the economic feasibility is measured. There are two alternatives proposed. The first alternative is to make a small change by renewing all equipment and modifying the business atmosphere. The second alternative is to make a bigger change by renewing all equipment and modifying the business atmosphere, as well as opening the stall earlier and enlarging the market range through a take-away-only branch in the center of the city. Those two alternatives are economically feasible. The rate of return difference between the two alternatives is relatively slight, but the second alternative has a slightly longer payback period but offers a chance for Warung Mobil Onosogrem to develop their production capacity and their market range that can be useful for further development.Keywords: MSMEs, car-restaurant, business development, economic feasibility